The Effect of Savings Shuttle Service Quality and Complaint Handling on Member Loyalty at BMT NU Muncar Branch - Nuraini, Septia; Imam Khusnudin (Al-Mashrafiyah: Jurnal Ekonomi, Keuangan, dan Perbankan Syariah, 2025)
This research aims to determine the influence of savings pick-up services and complaint handling on member loyalty at KSPPS BMT NU Muncar Branch, a Sharia microfinance institution. As an LKM (Microfinance Institution), BMT is designed to serve communities that are not yet reached by conventional banking services, providing financing for microenterprises, facilitating savings, and avoiding usurious practices. In its operations, BMT NU Muncar Branch focuses on increasing trust and member satisfaction as efforts to build member loyalty. This research employs a quantitative method with a descriptive approach, involving 67 samples from a population of 200 active members who utilize the savings pick-up service. The sample was determined using purposive sampling techniques, applying Slovin’s formula. Primary data were collected through questionnaires, while secondary data were obtained from related literature and journals. The independent variables in this study are the quality of savings pick-up services (X1) and complaint handling (X2), while the dependent variable is customer loyalty (Y), measured using a 4-point Likert scale. Data analysis was conducted using SPSS version 23, including statistical tests such as the Coefficient of Determination Test, F-Test, and T-Test. The results of this study are expected to provide insights for BMT NU Muncar Branch in enhancing competitiveness and operational sustainability by improving customer loyalty.